A study of laparoscopic cholecystectomy in rural setup - Barase, Avishkar K. (International Surgery Journal, 2018)
Background: Cholelithiasis is one of the major healthcare problems faced by the adult population all over the world. The disease prevalence is ever increasing because of the changing lifestyles and dietary habits. With emergence of laparoscopic cholecystectomy, it has become standard treatment modality for all kind of patients of gall stone disease. But still in India laparoscopic procedures are not routinely carried out in rural setup. So, we have decided to carry out this prospective study of laparoscopic cholecystectomy in rural setup mainly emphasizing on the cost benefit aspect and its impact on economical aspect of the rural government hospital as well as the patient’s financial burden. Methods: In this prospective randomized study, 60 patients of symptomatic cholelithiasis were grouped into open cholecystectomy (OC) and laparoscopic cholecystectomy (LC) groups randomly (30 each). The preoperative, intra operative and postoperative findings were noted and compared with each other and also with previous studies. The results are compared using paired t test and chi square test. Results: Laparoscopic cholecystectomy was better than open cholecystectomy in terms of less analgesic requirement, postoperative hospital stay, surgical site infection with better cosmetic outcome. The results were comparable regarding intra operative complications. Only duration of surgery was comparatively more in laparoscopic group. Thus, overall laparoscopic cholecystectomy was cost effective alternative as compared to open cholecystectomy. Conclusions: Laparoscopic cholecystectomy is better alternative to open cholecystectomy in term of less intra and postoperative complications as well as decreased financial burden on public health sector and patient point of view.